(untitled) (Simbiótica. Revista Eletrônica, 2022)
This text analyzes how Norbert Elias thinks about the influence of the processes of social development of knowledge in the constitution of sociology. We follow three steps. First, we demonstrate the concept of Process in Elias. Afterwards, we verify how the author understands the constitution of sociology. In the end, we show the relationship between the historical processes of knowledge production and the constitution of sociology. Here we will highlight the importance, according to Elias, of the evolution of knowledge with the long-term dynamics of social development and, also, of the composition of sociology as a relatively autonomous science. We start from the perspective that, for Elias, the constantly expanding social patrimony of knowledge enabled an adequate scientific method to analyze society. We use bibliographic research as a methodology. Thus, we will research a little explored point in Elias’ works. Keywords: Norbert Elias; knowledge; process; sociogenesis.